2021
DOI: 10.1038/s41405-021-00082-5
|View full text |Cite|
|
Sign up to set email alerts
|

Articaine in dentistry: an overview of the evidence and meta-analysis of the latest randomised controlled trials on articaine safety and efficacy compared to lidocaine for routine dental treatment

Abstract: Objectives To comprehensively review the existing studies of articaine in dentistry and conduct a systematic review and meta-analysis to answer the following Population, Intervention, Comparison and Outcome question: “Is articaine a safe and efficacious local anaesthetic for routine dental treatment compared to lidocaine?” Methods Database searches were conducted in Medline Ovid, Medline Pubmed, Scopus, Emcare, Proquest and the Cochrane Central reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 94 publications
(146 reference statements)
3
40
0
1
Order By: Relevance
“…However, systematic reviews aim to answer a novel question by combining and assessing all the available evidence, and we are very pleased to have published some highquality systematic reviews in 2021. These are evidently of interest to our readership as the paper by Martin et al 34 reviewing articaine in dentistry was the top accessed paper in BDJ Open in 2021. The paper by Johnson et al 36 on contamination by periodontal procedures was also highly viewed.…”
Section: Systematic Reviewsmentioning
confidence: 94%
See 1 more Smart Citation
“…However, systematic reviews aim to answer a novel question by combining and assessing all the available evidence, and we are very pleased to have published some highquality systematic reviews in 2021. These are evidently of interest to our readership as the paper by Martin et al 34 reviewing articaine in dentistry was the top accessed paper in BDJ Open in 2021. The paper by Johnson et al 36 on contamination by periodontal procedures was also highly viewed.…”
Section: Systematic Reviewsmentioning
confidence: 94%
“…There were four systematic reviews published in 2021, 33,34,35,36 with just two published in the whole of 2019-2020. BDJ Open is a research journal and so does not currently publish narrative reviews.…”
Section: Systematic Reviewsmentioning
confidence: 99%
“…Systematic reviews and meta-analysis are considered the highest, most robust analysis of clinical efficacy across multiple trials [ 7 , 8 ]. Multiple systematic reviews have been conducted on articaine efficacy and safety from 2010 to the present, none of them, nor any of the randomised controlled trials analysed by the reviews reported incidence of permanent nerve paraesthesia following articaine use [ 9 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The latest articaine systematic review with meta-analyses conducted by Martin et al in 2021 stated that articaine is a safe and efficacious LA for all routine dental treatment [ 12 ]. None of the participants in the 14 randomised controlled trials reported any major LA-related adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the commonly used dental anesthetics include 2% lidocaine and 4% articaine [ 3 , 21 , 22 , 23 , 24 ]. Although considerable evidence supports the safety and efficacy, mixed results also prevail, necessitating multicentric studies globally [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%